The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ani10112010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Rye Inclusion and Xylanase Supplementation on Structural Organization of Bone Constitutive Phases in Laying Hens Fed a Wheat-Corn Diet

Abstract: This study was conducted to examine the effect of dietary rye inclusion and xylanase supplementation on the bone quality of ISA Brown laying hens. Ninety-six laying hens were assigned to four groups: fed with wheat–corn diet or rye–wheat–corn diet (25% of hybrid rye inclusion) or nonsupplemented or supplemented with xylanase (200 mg/kg of feed) for a period of 25 weeks, from the 26th to the 50th week of age. X-ray absorptiometry, X-ray diffraction, and Fourier-transform infrared spectroscopy were used to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(105 reference statements)
5
8
0
Order By: Relevance
“…The current study also revealed an increased amount of immature collagen in trabecular and compact bone, which could indicate intense bone repair or bone turnover. The same result was observed in the medullary bone of the pre-laying hens, which is a secondary bone in the marrow cavity and plays a key role in the maintenance of bone homeostasis in layers during eggshell formation [36,41]. Besides an increase in the content of immature collagen in medullary trabeculae, we also observed an improvement in all the histomorphometrical parameters assessed.…”
Section: Discussionsupporting
confidence: 85%
“…The current study also revealed an increased amount of immature collagen in trabecular and compact bone, which could indicate intense bone repair or bone turnover. The same result was observed in the medullary bone of the pre-laying hens, which is a secondary bone in the marrow cavity and plays a key role in the maintenance of bone homeostasis in layers during eggshell formation [36,41]. Besides an increase in the content of immature collagen in medullary trabeculae, we also observed an improvement in all the histomorphometrical parameters assessed.…”
Section: Discussionsupporting
confidence: 85%
“…The current study investigated the effects of the inclusion of modern hybrid rye (Brasetto variety) to a corn–wheat-based diet, with or without xylanase supplementation, on the absorptive surface of the small intestine of broilers. Previous studies have shown that the use of rye, as an alternative energy source in poultry diets, has been associated with increased viscosity of the digesta and thus poor digestibility and absorption of ingested nutrients [ 8 ]. Rye inclusion, as well as xylanase supplementation, has yielded conflicting results with regards to their effects on the absorptive surface of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the utilization of rye in poultry diets has been shown to impair poultry performance [ 4 , 5 , 6 ] due to its high content of non-starch polysaccharides (NSPs), mainly in the form of arabinoxylans [ 7 ]. The limited capacity of monogastric animals to digest these NSPs results in increased digesta viscosity, decreased nutrient digestibility, slowed passage of the digesta through the gastrointestinal tract and the increased incidence of wet and sticky droppings [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a dearth of knowledge regarding the effects of substituting corn with hybrid rye and xylanase supplementation on bone and eggshell mechanical properties and mineralization which thus warrants investigation. Previously, we have shown the positive effects of xylanase supplementation on collagen maturity in the tibia of hens fed a wheat-corn diet with inclusion of 25% rye [18]. This indicated that the dietary inclusion of rye influenced bone homeostasis but did not provide any information regarding the effect of the diet on bone biomechanical properties or mineralization.…”
Section: Introductionmentioning
confidence: 94%
“…The conditions under which the hens were housed are described in detail in a previous publication [18]. Briefly, during the pre-experimental period, 96, 17-week-old, commercial ISA Brown laying hens were housed with two hens per cage, under climate-controlled conditions, in wire-mesh floor cages, and were fed a standard commercial diet.…”
Section: Experimental Designmentioning
confidence: 99%